The Case for Reforming Euro Area Entry Criteria - Zsolt Darvas (Hungarian Academy of Sciences, Institute of Economics, 2010)
The global economic and financial crisis has raised further concerns about the euro-entry criteria, in addition to other factors, such as the effective tightening of the criteria due to the enlargement of the EU from 12 to 27 members, the highly unfavourable property of business cycle dependence, the internal inconsistency of the criteria due to the structural price level convergence of Central and Eastern European countries, and the continuous violation of the criteria by euro-area members. The interest rate criterion became a highly volatile measure. Many US metropolitan areas would fail to qualify to be members of the US monetary union by applying the currently used inflation criterion to the US. It is time to reform the criteria and to strengthen their economic rationale within the legal framework of the EU treaty. A good solution would be to relate all criteria to the average of the euro area and simultaneously to extend the compliance period from the currently considered one year to a longer period.
Keywords: F33; F36; F53; 330; Euro; EU institutions; financial crisis; Maastricht-criteria; Eurozone; Konvergenzkriterien; Reform; EU-Mitgliedschaft